D-Dimer Test and Diagnosis of Deep Vein Thrombosis: A Comparative Study of 7 Assays - Elias, A; Aptel, I; Huc, B; Chale, J J; Nguyen, F; Cambus, J P; Boccalon, H; Boneu, B (Thrombosis and Haemostasis, 1996)
The current D-Dimer ELISA methods provide high sensitivity and negative predictive value for the diagnosis of deep vein thrombosis but these methods are not suitable for emergency or for individual determination. We have evaluated the performance of 3 newly available fast D-Dimer assays (Vidas D-Di, BioMerieux; Instant IA D-Di, Stago; Nycocard D-Dimer, Nycomed) in comparison with 3 classic ELISA methods (Stago, Organon, Behring) and a Latex agglutination technique (Stago). One-hundred-and-seventy-one patients suspected of presenting a first episode of deep vein thrombosis were investigated. A deep vein thrombosis was detected in 75 patients (43.8%) by ultrasonic duplex scanning of the lower limbs; in 11 of them the thrombi were distal and very limited in size (<2 cm). We compared the performance of the tests by calculating their sensitivity, specificity, positive and negative predictive value for different cut-off levels and by calculating the area under ROC curves. The concordance of the different methods was evaluated by calculating the kappa coefficient. The performances of the 3 classic ELISA and of the Vidas D-Di were comparable and kappa coefficients indicated a good concordance between the results provided by these assays. Their sensitivity slightly declined for detection of the very small thrombi. Instant IA D-Di had a non-significantly lower sensitivity and negative predictive value than the 4 previous assays; however its performance was excellent for out-patients. As expected, the Latex assay had too low a sensitivity and negative predictive value to be recommended. In our hands, Nycocard D-Dimer also exhibited low sensitivity and negative predictive value, which were significantly improved when the plasma samples were tested by the manufacturer. Thus significant progress has been made, allowing clinical studies to be planned to compare the safety and cost-effectiveness of D-Dimer strategy to those of the conventional methods for the diagnosis of venous thrombosis.